2017
DOI: 10.1007/s13365-017-0564-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR-155 associated with Toll-like receptors 3, 7, and 9 transcription in the olfactory bulbs of cattle naturally infected with BHV5

Abstract: Bovine herpesvirus 5 (BHV5) infection of young cattle is frequently associated with fatal neurological disease and, as such, represents an attractive model for studying the pathogenesis of viral-induced meningoencephalitis. Following replication in the nasal mucosa, BHV5 invades the central nervous system (CNS) mainly through the olfactory pathway. The innate immune response triggered by the host face to virus replication through the olfactory route is poorly understood. Recently, an upregulation of conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…This is the first study evaluating the effects of BoHV-5 infection in the absence of TLRs 3, 7 and 9 in C57BL/6 mice. There are few works analyzing the role of TLRs during acute bovine herpesvirus-5 infection and those works were restricted to in vitro or in vivo inoculation in cattle so far [33,34,39,43]. Calves infected by intranasal route with 10 6.3 TCID 50 of BoHV-5 showed an increase in the brain expression of TLRs 3, 7, 8 and 9 [34].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study evaluating the effects of BoHV-5 infection in the absence of TLRs 3, 7 and 9 in C57BL/6 mice. There are few works analyzing the role of TLRs during acute bovine herpesvirus-5 infection and those works were restricted to in vitro or in vivo inoculation in cattle so far [33,34,39,43]. Calves infected by intranasal route with 10 6.3 TCID 50 of BoHV-5 showed an increase in the brain expression of TLRs 3, 7, 8 and 9 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the negative miRNA-mRNA network revealed 12 significantly down-regulated miRNAs targeting these TLRs. It has been reported that some miRNAs, like miR-140-5p and welldescribed miR-155, could target TLRs to regulate the innate immune response during the virus infection that had subsequent impact on virus replication [38][39][40]. Upon recognition of pathogens, TLRs recruit a specific set of adaptor molecules, such as MyD88 (myeloid differentiation factor 88) and TIRAP, then initiate downstream signaling events that leads to the secretion of inflammatory cytokines, type I IFN, chemokines, and antimicrobial peptides [41].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miR-155 affects multiple physiological and pathological functions, including those related to viral infection. Recent studies provided evidence that miR-155 is involved in antiviral innate immunity through Toll-like receptors (TLR3, TLR7, and TLR9) or the nuclear factor kappa-B (NF-кB) signaling pathway [18][19][20]. The innate immune system provides an early phase defense to limit pathogen invasion by recognizing microbial moieties.…”
Section: Discussionmentioning
confidence: 99%